Measuring Alcohol Consumption Using Timeline Followback in Non-Treatment-Seeking Medical Clinic Patients With and Without HIV Infection: 7-, 14-, or 30-day Recall - Fiellin, David A. (Rutgers University, 2013)
OBJECTIVE: The measurement of alcohol consumption is an essential component of research in patients at risk for or infected with HIV. Daily estimation measures such as the Timeline Followback (TLFB) have been validated, yet the optimal time window and its performance in non-treatment-seeking medical clinic subjects and among those with HIV are not known. METHOD: In 1,519 HIV-infected and 1,612 uninfected men receiving medical care in general medical or infectious disease clinics, we compared the association between 7-, 14-, and 30-day TLFB reports, obtained via telephone, of alcohol consumption using Spearman’s correlation coefficients. To evaluate agreement between 7-, 14-, and 30-day reports of heavy episodic drinking, we evaluated percent agreement, sensitivity, and kappa statistics, considering 30-day report as the gold standard. RESULTS: The estimated prevalence of heavy episodic drinking was progressively higher for longer TLFB intervals (7 days: 6.3%; 14 days: 8.0%; 30 days: 9.5%). Correlation coefficients with 30- day TLFB were higher for 14 days (.94) than for 7 days (.86) overall (p < .001) and among HIV-infected (.94 vs. .86, p < .001) and uninfected (.95 vs. .87, p < 001). Correlations were similar by HIV status. When considered overall and by HIV status, the sensitivity, percent agreement, and kappa statistics are better for heavy episodic drinking based on 14 days compared with 7 days. CONCLUSIONS: A TLFB for alcohol consumption of 14 days is preferable to 7 days for non-treatment-seeking patients in medical clinics with and without HIV infection when compared with 30 days.